Uji Aktivitas Antibakteri Ekstrak Etanol Daun Matoa (Pometia Pinnata J. R & G.Forst.) terhadap Pertumbuhan Staphylococcus Aureus dan Escherichia Coli - Risna Risna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the antibacterial activity, effective concentration, and secondary metabolites in the ethanol extract of matoa left against the test bacteria Staphylococcus aureus and Escherichia coli. The research method extracts matoa leaf samples by maceration using 70% ethanol solvent, testing the antibacterial activity using the paper disk diffusion method. The results of the antibacterial activity test were then analyzed using the One way ANOVA method. The results showed that the diameter of the inhibition zone of the ethanol extract of matoa leaves on the growth of Staphylococcus aureus appeared to have a clear area at a concentration of 1%, 1.5%, and 2%, respectively, of 12.88 mm, 13.15 mm, 11.36 mm. In comparison, the results of measuring the diameter of the inhibition zone of the ethanol extract matoa leaf on the growth of Escherichia coli bacteria were seen to have a clear area at a concentration of 1%, 1.5%, and 2% of 9.5 mm, 10.23 mm, 12.1 mm respectively. This activity is thought to be due to the effects of alkaloid compounds, flavonoids, tannins, saponins, and steroids in the ethanol extract of matoa leaves. Based on the ANOVA test, a significance value of 0.000 <0.05 was obtained, so the results were significant. In conclusion, there are substantial differences in the use of various concentrations of matoa leaf extract on the growth of Staphylococcus aureus and Escherichia coli bacteria. Keywords: Antibacterial Activity, Matoa Leaves, Secondary Metabolites